Phase equilibria constraints on the melt fertility of crustal rocks: the effect of subsolidus water loss. (12th December 2014) - Webb, G.; Powell, R.; McLaren, S.
Abstract During regional prograde metamorphism, H2O generated by ongoing dehydration reactions is likely to be continuously lost from a rock by compaction. Classical melting experiments cannot easily simulate this phenomenon, because ideally, all run products are conserved within the experimental charge, although significant equilibration and H2O generation may occur during heating. Phase equilibria modelling is used to consider the effect of subsolidus water loss (SWL) on subsequent melting relationships of felsic lithologies (including metapelite, metagreywacke and metatonalite) in the suprasolidus. SWL drives the bulk composition towards the minimum saturation point on the boundary of the wet‐melting field and results in significantly reduced subsequent melt generation when compared to melting experiments involving conservation of subsolidus H2O. This effect is most significant at P–T conditions just above the solidus. For initially hydrated rocks, the reduction in melt production causes rheologically critical thresholds (e.g. melt connectivity threshold, melt escape threshold and the solid‐to‐liquid transition) to be intersected at temperatures generally more than 100 °C, higher than predicted by idealized experimental melting curves.